VALIDITY OF FLASH E-BOOK OF HUMAN LOCOMOTION SYSTEM FOR 2nd GRADE SENIOR HIGH SCHOOL - ZEIN FATA HUSNUL KARIMA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2017)
The human locomotion system describes about structure, mechanisms, and functions of human muscles and skeleton. The description of locomotion mechanism processes cannot be visualized by printed out or electronic books that have been circulating. Therefore a book that can display animation or video is needed. Advances in technology provide a solution in form of electronic book in Flash program that can display text, images, animation and video. This learning book can facilitate explanation of the concept to students. The purpose was to produce a Flash e-book of human locomotion system and to describe theoretical and empirical feasibility. 4-D (Define, Design, Develop and Disseminate) model used without Disseminate stage. Development of e-book was conducted in the Biology Department, Universitas Negeri Surabaya, and a limited trial was conducted in SMAN 20 Surabaya. Results showed that the theoretical feasibility of e-book got 100% or very feasible category while empirical feasible got 90% or very feasible. It can be concluded that the e-book developed in this study was feasible for use in the learning process. Keywords: e-book, flash, human locomotion system.